Extension of Ixodes ricinus ticks and agents of tick-borne diseases to mountain areas in the Czech Republic - Danielová, Vlasta; Rudenko, Natalia; Daniel, Milan; Holubová, Jaroslava; Materna, Jan; Golovchenko, Maryna; Schwarzová, Lucie (International journal of medical microbiology, 2006)
Along with the shift of the hard tick Ixodes ricinus to higher altitudes observed in the Czech Republic a corresponding shift of tick-borne infections to higher altitudes has been expected. Therefore, I. ricinus ticks, mainly nymphs, were investigated for the presence of tick-borne viruses, tick-borne encephalitis (TBE), Tribec and Eyach, and the spirochaete Borrelia burgdorferi sensu lato in the Sumava and Krkonose Mountains (Czech Republic). The TBE virus and different genospecies of B. burgdorferi s.l. were detected by RT-PCR and PCR, respectively. TBE virus was detected in ticks at 620 and 720 m above sea level (a.s.l.), B. burgdorferi s.l. was detected in ticks up to 1065 m a.s.l. Four genospecies of B. burgdorferi s.l. were identified, B. afzelii, B. garinii, B. burgdorferi sensu stricto, and B. valaisiana. Some nymphs carried multiple Borrelia infections. The conditions of tick-borne agents' distribution and potential epidemiological consequences are discussed.
Keywords: Geography; viry klíšťové encefalitidy; Encephalitis Viruses, Tick-Borne; Ixodes; hustota populace; klíště; zeměpis; Animals; Humans; Česká republika; Borrelia burgdorferi komplex; lidé; Altitude; Czech Republic; zvířata; Population Density; Borrelia burgdorferi Group; nadmořská výška